The impact of corporate sustainability management activities on customer satisfaction and loyalty in the shipping sector - Chua, Wei Xian (2015)
The topic of corporate sustainability has been gaining popularity among many management researchers as it grows in importance to the commercial world. In this paper, the impact that Corporate Sustainability Management Activities (CSMA) has on Customer Satisfaction (CS) and Customer Loyalty (CL) in the shipping industry will be studied in greater detail. CSMA consists of three dimensions - Economic, Environmental and Social. A thorough literature review was done on CSMA, CS and CL and a model illustrating the relationship between the three constructs in the shipping sector was drawn up. To test the accuracy of the model, three hypotheses were developed and they will be tested against the sample data collected. The three hypotheses are: H1: There is a positive correlation between CSMA and CS in Container Sector H2: There is a positive correlation between CS and CL in Container Sector H3: There is a positive correlation between CSMA and CL in Container Sector. Data will be collected from interviews with the maritime service providers, which were the shipping line. Data from the interviews will be analyzed qualitatively while data from the surveys will be analyzed quantitatively using Bivariate Regression Analysis, T-Test and ANOVA. From the results, H1 and H3 were supported that there was a positive correlation between CSMA on both CL and CS. In the elements of CSMA, economic activities have the greatest impact in both CS and CL, followed between both social and environmental. H2 was rejected that there was not a positive correlation which CS lead to CL. The main implication of this project is that it has opened a new research area on the potential activities of CSMA and the degree of influences it has on CS and CL. There are some limitations on the accuracy of the results. The main limitation is our poor response rate from the research, reducing our sample size. Thus any generalization from this research should be done with caution.